2016
DOI: 10.1016/j.neuroscience.2016.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Developmental ethanol exposure-induced sleep fragmentation predicts adult cognitive impairment

Abstract: Developmental ethanol exposure can lead to long-lasting cognitive impairment, hyperactivity, and emotional dysregulation among other problems. In healthy adults, sleep plays an important role in each of these behavioral manifestations. Here we explored circadian rhythms (activity, temperature) and slow-wave sleep in adult mice that had received a single day of ethanol exposure on postnatal day 7 and saline littermate controls. We tested for correlations between slow-wave activity and both contextual fear condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 84 publications
(142 reference statements)
8
41
0
Order By: Relevance
“…As photic phase-resetting is the primary mechanism by which circadian rhythms are synchronized to the environment, this suggests that adolescent mice may be relatively resilient to the chronodisruptive effects of acute ethanol. This insensitivity is consistent with the only other study of which we are aware that examines the effect of developmental ethanol exposure on circadian endpoints, which reports changes in slow-wave sleep, but not circadian activity or temperature rhythms, in mice exposed to ethanol on postnatal day 7 (Wilson et al, 2016). It is also noteworthy that adolescent rats are initially less sensitive to ethanol-induced sleep disruption (Ehlers et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…As photic phase-resetting is the primary mechanism by which circadian rhythms are synchronized to the environment, this suggests that adolescent mice may be relatively resilient to the chronodisruptive effects of acute ethanol. This insensitivity is consistent with the only other study of which we are aware that examines the effect of developmental ethanol exposure on circadian endpoints, which reports changes in slow-wave sleep, but not circadian activity or temperature rhythms, in mice exposed to ethanol on postnatal day 7 (Wilson et al, 2016). It is also noteworthy that adolescent rats are initially less sensitive to ethanol-induced sleep disruption (Ehlers et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…Using a similar dose of alcohol (2.5 g/kg; administered twice over a 2 h interval) PAE paradigm, Smiley et al observed a reduction in total brain volume (~10%), including in frontal cortex neurons (parvalbumin and calretinin GABAergic neurons; ~30%) in PN72–89 mice (Smiley et al 2015). In a follow-up study using the same PAE paradigm, adult PAE mice exhibited hyper-activity in their home cages, reduced and fragmented slow-wave sleep, and reduced slow-wave sleep duration (Wilson et al 2016). Furthermore, PAE mice exhibited impaired contextual fear conditioning memory that was significantly correlated with slow-wave sleep fragmentation (Wilson et al 2016).…”
Section: Mouse Models Of Prenatal Alcohol Exposurementioning
confidence: 99%
“…In a follow-up study using the same PAE paradigm, adult PAE mice exhibited hyper-activity in their home cages, reduced and fragmented slow-wave sleep, and reduced slow-wave sleep duration (Wilson et al 2016). Furthermore, PAE mice exhibited impaired contextual fear conditioning memory that was significantly correlated with slow-wave sleep fragmentation (Wilson et al 2016). Interestingly, mice with impairments in GABA A receptors (or their subunits) have learning and memory deficits, hyperactivity, and dysregulated sleep patterns, impairments reminiscent of mouse models of acute third trimester PAE (DeLorey et al 1998; Volgin 2008).…”
Section: Mouse Models Of Prenatal Alcohol Exposurementioning
confidence: 99%
“…Such ethanol-induced brain damage in neonates results in long-lasting brain structural [ 24 , 25 , 27 , 29 ] and behavioral abnormalities [ 9 , 31 , 32 ]. Even one day of acute ethanol exposure, which induces robust apoptosis [ 10 , 11 ], results in abnormalities in cellular, structural, physiological, and behavioral levels in the adult brain [ 25 , 26 , 27 , 29 , 30 , 31 , 32 ].…”
Section: Glial Activation Is Associated With Neurodegeneration In mentioning
confidence: 99%
“…For instance, binge-like ethanol exposure in early postnatal rodents during the period equivalent to the third trimester of human pregnancy induces robust neurodegeneration [ 7 , 8 , 9 , 10 , 11 ], because neurons are particularly vulnerable to environmental toxins during this period of heightened synaptogenesis [ 12 ]. This ethanol-induced neurodegeneration, which is associated with glial activation [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ] and elevation of pro- and anti-inflammatory cytokines [ 13 , 20 , 21 , 22 , 23 ], may result in long-lasting cellular, physiological, and neurobehavioral deficits [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. It is conceivable that ethanol-induced glial activation/neuroinflammation in animal models of FASD is involved in the long-lasting brain damage, as reported in various neurodegenerative diseases [ 33 ] and brain injuries [ 34 ].…”
Section: Introductionmentioning
confidence: 99%